On the trace space of a Sobolev space with a radial weight - Helmut Abels; Miroslav Krbec; Katrin Schumacher (Journal of Function Spaces and Applications)
Our concern in this paper lies with trace spaces for weighted Sobolev spaces, when the weight is a power of the distance to a point at the boundary. For a large range of powers we give a full description of the trace space.